The dramatic story of Léon and Camille: literary geography essay set in the boulevards of Brussels - Tatiana Debroux; Laurence Brogniez; Jean-Michel Decroly; Christophe Loir (Brussels Studies)
The spatial analysis of a literary text published in the mid 19th century allows a rediscovery of the panoramic literature genre and the wealth of information it provides about the urban context in which it was born. Through a literary geography essay based on the singular narrative of a condemned love, we wish to show the relevance of interdisciplinary thought on space and artistic productions, which are best understood when explored from different perspectives. The narrative studied here is built around the boulevards of Brussels and their social use: the analysis of places, temporality, characters’ journeys and their cartographic translation reveals the sociospatial structuring of the city as a whole. It also provides precious information concerning the use of space and its representations, which traditional historical sources are unable to do.